Chelation controlled regiospecific O-substitution of myo-inositol orthoesters: convenient access to orthogonally protected myo-inositol derivatives - Devaraj, Subramanian; Shashidhar, M. S.; Dixit, Shailesh S. (Tetrahedron, 2005)
A general method for the completely regioselective protection of the three secondary hydroxyl groups of orthoester derivatives of myo-mositol, utilizing the subtle differences in reactivity exhibited by its alkali metal alkoxides due to differences in their ability to form chelates, is described. This method provides convenient access to orthogonally protected myo-inositol derivatives. A comparison of the methylation of racemic 4-0-trityl-myo-inositol 1,3,5-orthoformate in the presence of sodium or lithium ions showed that stabilization of the C4-alkoxide by chelation with lithium overrides steric hindrance offered by the C6-axial substituent in deciding the regioselectivity during the nucleophilic O-substitution. (C) 2004 Elsevier Ltd. All rights reserved.

Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex

Inositol derived crown ethers: effect of auxiliary protecting groups and the relative orientation of crown ether oxygen atoms on their metal ion binding ability - Dixit, Shailesh S.; Shashidhar, Mysore S. (Tetrahedron, 2008)
The binding constants of crown ethers prepared from tetra-O-substituted myo- and scyllo-inositol derivatives and 2-O-substituted myo- and scyllo-inositol-1,3,5-orthoformates, with metal picrates show that the O-substituents and the relative orientation of the crown ether oxygen atoms contribute significantly to the binding of crown ethers with metal ions. In particular, the binding efficiency of myo-inositol derived crown ethers to silver and potassium ions could be enhanced by introducing benzyl ethers in the inositol ring. Hence binding efficacy and selectivity of metal ions to inositol derived crown ethers can be tuned by varying substituents on the myo-inositol ring and/or the relative orientation of crown ether oxygen atoms. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; metal complex; supramolecule

Anti-oxidant properties of ficus religiosa L. Bark extract on human keratinocytes - Dixit, Shailesh S.; Kulkarni, Atul; Seo, Hyo Hyun; Gadgil, Jayant; Dingre, Medini; Umar, Ahmad; Moh, Sang Hyun; Parasharami, Varsha A. (Science of Advanced Materials, 2016)
Ficus religiosa (Sacred Fig) is a medicinally important tree, native to the Indian subcontinent. It has been extensively pharmacologically researched species having wide spectrum of medicinal properties. All parts of F. religiosa tree are known to possess important medicinal properties such as anti-oxidant, anti-inflammatory, wound healing and skin diseases etc. However, effects of F. religiosa on skin cells line HaCaT was not studied for its antioxidant properties. In this report we have investigated F. religiosa bark aqueous extract for its antioxidant properties on human keratinocytes (HaCaT) cell line using DPPH, superoxide dismutase 1, superoxide dismutase 2 and catalase assay. We observed that F. religiosa bark aqueous extract efficiently scavenged (80%) DPPH radicals. Superoxide dismutase1 assay of F. religiosa bark aqueous extract effectively scavenged superoxide radicals (O-2(-)) and showed dose dependent activity. Reactive oxygen species were trapped by superoxide dismutase 2 assay of F. religiosa bark aqueous extract and form hydrogen peroxide. Catalase assay results revelled that hydrogen peroxide was further decomposed to give water and oxygen. Thus various anti-oxidant assays of F. religiosa bark aqueous extract indicate that it efficiently reduced the reactive oxygen species in skin cells.
Keywords: Anti-Oxidant; Catalase Assay; DPPH Assay; Ficus religiosa; Keratinocyte HaCaT Cell Line; Moraceae; SOD Assay